PENGUATAN PENDIDIKAN KARAKTER MANDIRI PESERTA DIDIK PADA MATA PELAJARAN EKONOMI DI SMAN 5 SINGKAWANG - Tuti Sunita; Sulistyarini Sulistyarini; Endang Purwaningsih (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis study aims to determine the strengthening of independent character education of student in economic subject at SMAN 5 Singkawang. The research method used is descriptive qualitative research method. The data source of this study was one economics teacher at SMAN 5 Singkawang. Data collection techniques used were observation and interview. The data namely collection, reduction, display, and drawing conclusions. The resulth of this study indicate that the strengthening of character education has been implemented in schools since 2016, the condition PPK at the school is already quite good, fox example studens are able to do their own tasks, and this is because of the cooperation between the principal and teachers, although not yet optimal, indicators of teacher success in implementing PPK it is seen from students who have been able to obey the rules made by teachers, teachers from schools have tried their best to strengthen the independent character of the students though classroom management and the use of appropriate learning methods such as PBL, group discussion, and teachers still feel have obstacles in implementing the reinforcement of character education, especially independent character in the learning process because it must be appropiate with the material, methods and obstacles that come from the student themselves.       Keywords: Economic Subjects, Independent, Strengthening Character Education.